Mutations in Exon 11 of c-Kit Occur Preferentially in Malignant versus Benign Gastrointestinal Stromal Tumors and Do Not Occur in Leiomyomas or Leiomyosarcomas - Lasota, Jerzy (American Society for Investigative Pathology, 1999)
Gastrointestinal stromal tumors (GISTs) comprise the largest subset of mesenchymal tumors of the gastrointestinal tract. These neoplasms differ histologically and immunohistochemically from typical leiomyomas and leiomyosarcomas. Most GISTs express CD34 and CD117 (c-kit protein) but not desmin. Recently, gain-of-function mutations of c-kit proto-oncogene have been shown in five solitary GISTs and in tumors and leukocytes from a family with multiple GISTs. An in-frame deletion or a point mutation in exon 11 of c-kit was detected in these cases. Stable transfection of the mutant c-kit complementary DNA was also shown to induce malignant transformation of murine lymphoid cells, suggesting that the c-kit mutations contribute to tumor development. In this study, we evaluated 43 GISTs and 14 smooth muscle tumors for mutations in the exon 11 of c-kit by a PCR-assay. Half of the malignant GISTs (12/24) and only one benign GIST (1/19) revealed mutant bands. No mutant bands were found in 3 leiomyomas and 11 leiomyosarcomas. Sequence analysis confirmed the presence of an in-frame deletion of 3–21 bp in all 13 GISTs with mutant bands. Wild-type bands from 8 malignant and 11 benign GISTs and 7 smooth muscle tumors without mutant bands were cloned and sequenced. Additional mutations were found in 3 malignant and 2 benign GISTs. There were no mutations in 3 leiomyomas and 4 leiomyosarcomas. The mutation status of exon 11 did not correlate with immunohistochemically detectable expression of the CD117, as virtually all GISTs with or without such mutations showed CD117 immunoreactivity. The c-kit mutations occur preferentially in malignant GISTs and might be a clinically useful adjunct marker in the evaluation of GISTs. The conservation of the c-kit mutation pattern, observed in consecutive lesions from the same patients, suggests that these mutations might be useful tumor markers in monitoring recurrence or minimal residual disease.